Putusan Hakim Mahkamah Agung tentang Dispensasi Kawin (Dispensasi Kawin dalam Sistem Hukum Indonesia) - Ahmad Nailul Mubarok; R. Zainul Mushthofa (JOSH: Journal of Sharia, 2024)
This article discusses the process of examining marriage dispensation cases prior to and following the enactment of Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Cases. This paper was written using a qualitative research method, specifically normative and empirical juridical approaches. According to the findings of this study, the provisions of Supreme Court Regulation Number 5 of 2019 have explicitly regulated several things that are not specifically regulated in the formal and material rules governing marriage dispensation. The adoption of this regulation is anticipation and standardization for judges in making legal decisions so that court decisions pay more attention to the best interests of children when granting a marriage dispensation application.